The Development and Validation of STEM-Based Learning Devices on Hydrostatic Pressure Material to Train Science Process Skills - Sjahrir, A; Supardi, Z A I; Cahyaningrum, S E (International Journal for Educational and Vocational Studies, 2020)
Nowadays, the 21st Century learning demands in which integrated technology in learning is common. Learning with the STEM approach (Science, Technology, Engineering and Mathematics) answers the demands of learning in the 21st century. The aim of this study is to describe the results of the validation of learning tools developed, in terms of practicality of learning devices reviewed from the activities of students during learning, while in terms of the effectiveness of learning devices reviewed from the results of students' science process skills. The method used in the 4D development research was adapted. During the field trial phase, 30 research subjects were used in the eighth grade students. The data analysis technique used is descriptive quantitative and qualitative. Learners conduct hydrostatic pressure experiments, the measured process skills component formulating the problem, formulating hypotheses, identifying variables, interpreting data and drawing conclusions. Science process skills test in the form of essay questions on material pressure substances that are in accordance with predetermined SPS (Science Process Skills) components. The results of the validation of the learning tools obtained a score of 3. 81 very valid categories and feasible to be used as teacher reference in learning, the results of the practicality of the learning tools obtained the highest activity of students conducting experiments reaching a percentage of 35%, while the effectiveness of the learning devices obtained the highest SPS (Science Process Skills) results interpreting the data component of 99%.